Generation of Soil Site Suitability Maps for Major Crops Grown in Nethakuppam Watershed of Ramachandrapuram Mandal in Chittor District Using RS and GIS - Rajeswari, B.; Reddy, P. V. R. M.; Nagamadhuri, K. V.; Reddiramu, Y. (International Journal of Economic Plants, 2021)
Composite surface soil samples (0-15 cm) were collected from 250 sites across Nethakuppam watershed of Ramachandrapuram mandal in Chittoor district of Andhra Pradesh using Arc Map software with the grid size of 10 ha. The GPS data at each sample location was collected.A study was undertaken to evaluate their soil site suitability forRice, Sugarcane and Ground nut.The soil site suitability maps for rice, sugarcane and groundnut delineate the areas in to suitable and not suitable which could be utilized for selecting the proper cropping pattern at local level. Suitability analysis of rice crop in study area indicated 92 ha is highly suitable (S1), 648 ha is moderately suitable (S2) and 1508 ha is marginally suitable (S3). The remaining area of 23 ha is having severe limitations that preclude the growing of rice making it not suitable (N). Soil sitesuitability maps for sugarcane crop in study area indicated that about 880 ha is highly suitable (S1), 1386 ha is moderately suitable (S2) and soil siteSuitability analysis of groundnut crop in Nethakuppam indicated that about 1713 ha is highly suitable (S1), 526 ha is moderately suitable (S2) and the remaining area of 23 ha is marginally suitable (S3). it can be summarized that new technologies of remote sensing, GIS and GPS have opened a new era in generating natural resource database to integrate and assess their potential on spatial basis. Integration of GIS with various models in the present study was highly useful in generating the soil suitability assessment.